The Implementation of Love Sensory Stimulation Method in Teaching Autistic Students - Eva Merryanti; Gatot Sutapa Yuliana; Regina Regina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aimed to find depth insight into the implementation of love sensory in teaching English to autistic students and subsequently the impact of its implementation on their learning achievement. The research subjects are students who have problems understanding instructions, interacting, and communicating. The data collected in this research is qualitative and was collected through observation and interviews. There are some findings found such as the behavior of autistic students that is seen in the teaching and learning process such as difficulty in understanding instructions and interacting, and ignoring their learning environment are specific symptoms of Autistic Syndrome Disorder. The symptoms shown by autistic students are the cause of failure in the learning process. However, the implementation of love sensory stimulation can change the behavior of autistic students. This method can help autistic students adapt and learn together with normal students. So, autistic students’ progress in learning and have achieved their learning goals. The expectation is to provide contributions to parties in need, including teachers who teach autistic students, parents, and future researchers. Based on the findings can be concluded that autistic students can develop in their learning process and interact in their social environment if they are guided in the right way.